INDIVIDUAL PERFORMANCE AS A FACTOR FOR INCREASING EMPLOYEE PRODUCTIVITY - Liya Triyani; Nurrina Zulfa; Dinda Adilla; Aria Mahardika; Silvia Afnes (CV. Doki Course and Training, 2023)
Employee productivity is very important in supporting the sustainability and advancement of a company, this cannot be separated from the involvement of the workforce in the process, good employee performance can affect the company's productivity. This study aims to find out Individual Performance Relationship with Employee Work Productivity at PT Financially Multi Finance Kreditplus Palembang. The respondents involved in this study were as many as 32 respondents, which were randomly chosen using data collection techniques through questionnaires. Using correlational quantitative research methods. From the results of the study conducted show that the two variables between individual performance and employee work productivity have a strong relationship, employee performance encourages employee productivity.